(untitled) (Global Journal of Management and Business Research, 2015)
The controversial issues of employee motivation and wage expectation formation are often analysed in scientific and practical planes by addressing to the fact that a prospective employee (especially with no work experience) may be employed with preformed wrong wage expectations. The paper aims to assess the problematic aspects of the integration of young age (18-23 years old) persons, studying in the university, into the labour market associated with the expectations of desired wage.